Differential Measurement for Cavity Ring-Down Spectroscopy with Dynamic Allan Variance - Zeqiang Mo; Jin Yu; Jinduo Wang; Jianguo He; Shoujun Dai; Yang Liu (Journal of Spectroscopy)
The method of dynamic Allan variance (DAVAR) is used to analyze the time-varying characteristics of a nonstationary signal and is thus incorporated to evaluate the random error in the cavity ring-down spectroscopy (CRDS) experiments. With the numerical simulation of the influence of instabilities of sudden, slow, or periodic changes on the measurement accuracy in the ring-down process, DAVAR is proved to be an effective way to evaluate random error characteristics in an interfering environment. In order to minimize influences of time-varying noises in CRDS, a practical differential measurement method is proposed, in which wavelength modulation is applied to detect the ring-down times at the absorption peak and the nonabsorption peak in a time-division manner. The validity of the differential measurement is proved with its ability to compensate the influence of the environment changes and improves the accuracy from 0.181 ppm to 0.00914 ppm. The differential measurement method can be used to correct the time-varying error in real time and is helpful to improve the environmental adaptability of the CRDS instrument.